A survey on the sawflies (Hymenoptera: Symphyta) of Gorgan County of Golestan Province in northern Iran - Roya Mohammadkhani; Ahmad Nadimi; Mohammad Khayrandish (Journal of Insect Biodiversity and Systematics, 2019)
A survey on sawflies (Hymenoptera: Symphyta) fauna of Gorgan County, northern Iran, during 2015-2017, led to the identification of sixteen species. Six species including Arge cingulata (Jakowlew, 1891); Calameuta pallipes (Klug, 1803); Phylloecus xanthostoma (Eversmann, 1847); Allantus cingulatus (Scopoli, 1763); Ametastegia pallipes (Spinola, 1808) and Nematus lucidus (Panzer, 1801) are recorded for Golestan fauna for the first time and C. pallipes is a new record for the Iranian fauna.